PENGARUH JENIS KELAMIN TERHADAP STATUS FAALI KAMBING KACANG - Padang, Padang (FAPETKAN UNTAD, 2011)
This study was conducted at experimental pens from May 19th to August 11st 2005, for 10 weeks in Pengawu village, South Palu district, Palu Regency, Central Sulawesi Province. This study aims at determining effect of sex on body temperature, pulse and respiration frequencies of Kacang goat. The experimental animal used consisted of 15 male goats and 15 female goats, aged around 10 months old with their body weight between 10.10 and 16.10 kg from local farmer at Palu Regency and its surroundings. The animals were placed at 30 individual pen of 75 X 75 X 75 cm. Each pen was equipped with feed and water troughs. Data collected were analyzed and tested with T – test with consisting of two treatments Kj (Male Kacang goat) and Kb (female kacang goat). Statistical analysis of T-Test indicated that body temperature, respiration frequency and pulse frequency of male goat were higher (P<0.05) those of female Kacang Goat. Key words : Body temperature, pulse frequency, sex and respiration frequency.